Biopesticides: a sustainable approach for pest management: Biopesticides in sustainable pest management - Parajuli, Sovit; Shrestha, Jiban; Subedi, Sudeep; Pandey, Meena (SAARC Journal of Agriculture, 2022)
Biopesticides are an important component of Integrated Pest Management (IPM) programs for insect pest control since they are more natural, environmentally friendly, safer than chemical pesticides and have relatively no or little effect on non-target organisms. They aid in improving crop health and yields while lowering production costs and eliminating the usage of toxic chemicals. They are effective tools for creating new sustainable agricultural products. Several botanicals and microbial biopesticides have been identified, isolated, processed, and used to eliminate hazards caused by Coleopteran, Hemipteran, Dipteran, Lepidopteran, Hymenopteran, and Thysanopteran insects. Several species of botanicals such as Neem (Azadirachta indica A.), Chili pepper (Capsicum annuum), Garlic (Allium sativum), Moringa (Moringa oleifera), Clove basil (Ocimum gratissimum), China berry (Melia azedarach), bitter leaf (Vernonia amygdalina) etc. and microbes such as Bacillus thuringiensis, Beauveria bassiana, Metarhizium anisopliae, Baculovirus (nucleopolyhedrovirus (NPV) and granulovirus (GV) ), Steinernema carpocapsae, Nosema, etc. have been used as biopesticides. Because biopesticides are successful in managing insect pests and diseases while also being safe to humans and the environment, they must be manufactured in the country and made available to farmers. SAARC J. Agric., 20(1): 1-13 (2022)